Signatures in the conductance for phase transitions in excitonic systems - Soller, Henning; Breyel, David (Modern physics letters, 2013)
In this paper, we analyze two phase transitions in exciton bilayer systems: a topological phase transition to a phase which hosts Majorana fermions and a phase transition to a Wigner crystal.